2020
DOI: 10.1590/2317-1545v42234256
|View full text |Cite
|
Sign up to set email alerts
|

Seed priming with salicylic acid potentiates water restriction-induced effects in tomato seed germination and early seedling growth

Abstract: Seed priming with salicylic acid (SA) has been described as a method with potential to improve seed germination under unfavorable conditions. The present study aimed to evaluate the ability of seed priming with SA to attenuate the impact of water restriction during germination and early seedling growth of tomato. Seeds were subjected to different concentrations of SA (0, 25 and 50 µM) and sowed on substrates at different percentages of the water holding capacity (20, 30, 40 and 100%). The following variables w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 41 publications
0
8
0
1
Order By: Relevance
“…So, +SA-seed can induce characteristics that are beneficial during water restriction conditions allowing the maintenance of a larger photosynthetic area and allocation of resources to the roots that assist in the absorption of water and nutrients (Jangid and Dwivedi 2017). A large number of works have indicated that SA enhances growth attributes -leaf area and dry matter production -in tomato when exposed to water stress (El-Hady et al 2021;Galviz-Fajardo et al 2020;Gharbi et al 2018;Lobato et al 2021). Effects on root growth must be carefully considered, Abbasi et al (2020) highlight that SA improved and kept the root system of cucumber plants, improving the absorption of nutrients, increasing the carbohydrate content of flowers and fruits, all this resulting in the increased number and size of fruits.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…So, +SA-seed can induce characteristics that are beneficial during water restriction conditions allowing the maintenance of a larger photosynthetic area and allocation of resources to the roots that assist in the absorption of water and nutrients (Jangid and Dwivedi 2017). A large number of works have indicated that SA enhances growth attributes -leaf area and dry matter production -in tomato when exposed to water stress (El-Hady et al 2021;Galviz-Fajardo et al 2020;Gharbi et al 2018;Lobato et al 2021). Effects on root growth must be carefully considered, Abbasi et al (2020) highlight that SA improved and kept the root system of cucumber plants, improving the absorption of nutrients, increasing the carbohydrate content of flowers and fruits, all this resulting in the increased number and size of fruits.…”
Section: Discussionmentioning
confidence: 99%
“…Although many studies report that SA has the ability to induce drought tolerance by increasing antioxidant activity (El-Hady et al 2021;Hayat et al 2008;Lobato et al 2021), many others also point out that it is not a general response (Bortolin et al 2020;El-Esawi et al 2017). Furthermore, Saruhan et al (2012) reported that this is a SA-induced mechanism of water stress tolerance, consequence of the ability of SA molecule to bind to CAT and to inhibit its activity while intensifying SOD activity (Razmi et al 2017;Galviz-Fajardo et al 2020) and finally results in enhanced H 2 O 2 levels as the ones observed in leaves and roots with +SA-seed. Huang et al (2019) point out that SA inhibits the expression of ROS scavenging-related genes, which increases ROS levels and promotes root meristem activity, promoting root growth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Considerando que la RSA involucra un incremento del contenido endógeno en tejidos vegetales del AS, y puesto que ha sido evaluado la aplicación exógena para aplicar protección en contra de varios tipos de estreses bióticos (Fan et al 2009;Rangel Sánchez et al 2010;Sanchez Rojo 2010;Galviz-Fajardo et al 2020;Maia Junior et al 2020)y abióticos, tales como altas y bajas temperaturas, salinidad o metales pesados en una multiplicidad de patosistemas (Gunes et al, 2007;Chávez-Suarez et al, 2012;Bernardo 2016).…”
unclassified